Capsaicin topical cream (8%) for the treatment of myofascial pain syndrome - Romero, Valéria [UNESP]; Lara, Juliana Rodrigues [UNESP]; Otero‐Espinar, Francisco; Salgado, Manoel Henrique [UNESP]; Modolo, Norma Sueli Pinheiro [UNESP]; Barros, Guilherme Antonio Moreira de [UNESP] (Elsevier, 2019)
Background: Myofascial pain syndrome is a common cause of musculoskeletal pain. The objective of this study was to evaluate the potential analgesic action of 8% capsaicin cream for topical use in patients with myofascial pain syndrome. Methods: Initially, cream formulations of PLA (Placebo) and CPS (Capsaicin 8%) were developed and approved according to the current requirements of the health authority agency. The 40 participating patients were randomly assigned to the PLA and CPS groups in a double‐blind fashion. Before the creams were topically administered, according to the allocation group, the local anesthetic was used for a period of 50 minutes directly in the area of interest. The cream was applied to the area of the skin over the trigger point, represented by the area with pain at palpation, in an amount of 10 g for 30 minutes in a circular area of 24 mm diameter. Subsequently, the cream was removed and the skin tolerability parameters were evaluated. The pain was measured before and during the formulation application, as well as at 1 hour, 7 days, 30 days, and 60 days after the procedure, evaluated using a verbal numerical scale (from 0 to 10: with 0 = no pain and 10 = worst pain imaginable). Results: No patient in PLA Group had hyperemia or burning sensation at the site of application, while 85% of patients in CPS Group had hyperemia or burning sensation at 15 minutes. These complaints disappeared 24 hours after the cream was removed. The pain score in CPS Group decreased steadily up to the 60th day of evaluation (p < 0.0001). Conclusion: Application of the formulations did not cause macroscopic acute or chronic skin lesions in patients, and the 8% capsaicin formulation was beneficial and well tolerated.
Creme tópico de capsaicina (8%) para o tratamento da síndrome da dor miofascial
Keywords: Capsaicin; Myofascial pain syndrome; Topical route; Trigger points